High potency multistrain probiotic improves liver histology in non-alcoholic fatty liver disease (NAFLD): a randomised, double-blind, proof of concept study - Ashim Das; Ajay Duseja; Subrat K Acharya; Manu Mehta; Shruti Chhabra; Satyavati Rana; Siddhartha Dattagupta; Radha K Dhiman; Yogesh K Chawla (BMJ Open Gastroenterology)
Objective Pharmacological treatment of non-alcoholic fatty liver disease (NAFLD) is still evolving. Probiotics could be a promising treatment option, but their effectiveness needs to be established. The present study aimed to evaluate the efficacy of a high potency multistrain probiotic in adult patients with NAFLD.Methods Thirty-nine liver biopsy-proven patients with NAFLD were randomised in a double-blind fashion to either lifestyle modifications plus an oral multistrain probiotic (675 billion bacteria daily, n=19) or identical placebo (n=20) for 1 year. Lifestyle modifications included regular exercise for all and control of overweight/obesity (with additional dietary restrictions), hypertension and hyperlipidaemia in those with these risk factors. Primary objective of the study was the histological improvement in NAFLD activity score (NAS) and its components and secondary objectives were improvement in alanine transaminase (ALT) and cytokine profile.Results Thirty (76.9%) out of 39 patients with NAFLD completed the study with 1 year of follow-up. A repeat liver biopsy at 1 year could be done in 10 patients (52.6%) in probiotic group and five patients (25%) in placebo group. In comparison to baseline, hepatocyte ballooning (p=0.036), lobular inflammation (p=0.003) and NAS score (p=0.007) improved significantly at 1 year in the probiotic group. When compared with placebo, the NAS score improved significantly in the probiotic group (p=0.004), along with improvements in hepatocyte ballooning (p=0.05) and hepatic fibrosis (p=0.018). A significant improvement in levels of ALT (p=0.046), leptin (p=0.006), tumour necrosis factor-α (p=0.016) and endotoxins (p=0.017) was observed in probiotic group in comparison to placebo at 1 year. No significant adverse events were reported in the study.Conclusion Patients with NAFLD managed with lifestyle modifications and multistrain probiotic showed significant improvement in liver histology, ALT and cytokines.Trial registration number The clinical trial is registered with CLINICAL TRIAL REGISTRYINDIA (CTRI); http://ctri.nic.in, No. CTRI/2008/091/000074